Complementarity between the updated version of the front-of-pack nutrition label Nutri-Score and the food-processing NOVA classification - Barthélemy Sarda; Emmanuelle Kesse-Guyot; Valérie Deschamps; Pauline Ducrot; Pilar Galan; Serge Hercberg; Melanie Deschasaux-Tanguy; Bernard Srour; Leopold K Fezeu; Mathilde Touvier; Chantal Julia (Cambridge University Press, 2024)
Abstract Objective: To compare the initial and the updated versions of the front-of-pack label Nutri-Score (related to the nutritional content) with the NOVA classification (related to the degree of food processing) at the food level. Design: Using the OpenFoodFacts database - 129,950 food products - we assessed the complementarity between the Nutri-Score (initial and updated) with the NOVA classification through a correspondence analysis. Contingency tables between the two classification systems were used. Settings: The food offer in France. Participants: Not applicable. Results: With both versions (i.e. initial and updated) of the Nutri-Score, the majority of ultra-processed products received medium to poor Nutri-Score ratings (between 77·9 % and 87·5 % of ultra-processed products depending on the version of the algorithm). Overall, the update of the Nutri-Score algorithm led to a reduction in the number of products rated A and B and an increase in the number of products rated D or E for all NOVA categories, with unprocessed foods being the least impacted (-3·8 percentage points (-5·2 %) rated A or B and +1·3 percentage points (+12·9 %) rated D or E) and ultra-processed foods the most impacted (-9·8 percentage points (-43·4 %) rated A or B and +7·8 percentage points (+14·1 %) rated D or E). Among ultra-processed foods rated favourably with the initial Nutri-Score, artificially sweetened beverages, sweetened plant-based drinks and bread products were the most penalised categories by the revision of Nutri-Score while low-sugar flavoured waters, fruit and legume preparations were the least affected. Conclusion: These results indicate that the update of the Nutri-Score reinforces its coherence with the NOVA classification, even though both systems measure two distinct health dimensions at the food level.